"It's not black and white": Public health researchers' and ethics committees' perceptions of engaging research participants online. Issue 1 (4th February 2019) - Crawford, Sharinne; Hokke, Stacey; Nicholson, Jan M.; Zion, Lawrie; Lucke, Jayne; Keyzer, Patrick; Hackworth, Naomi
Abstract : Purpose: The internet offers an opportunity for researchers to engage participants in research in a cost-effective and timely manner. Yet the use of the internet as a research tool (internet research) comes with a range of ethical concerns, and the rapidly changing online environment poses challenges for both researchers and ethics committees. The purpose of this paper is to highlight the key ethical issues of using the internet to recruit, retain and trace participants in public health research, from the perspectives of researchers and human research ethics committee (HREC) members. Design/methodology/approach: This study employed a qualitative design using semi-structured interviews with eight public health researchers and seven HREC members in Australia to explore the key ethical issues of using the internet to engage research participants. Findings: The study identified commonalities between researchers and HREC members regarding the utility and ethical complexity of using the internet to recruit, retain and trace research participants. The need for guidance and support regarding internet research, for both groups, was highlighted, as well as the need for flexibility and responsiveness in formal ethical processes. Originality/value: This research contributes to the understanding of how the internet is used to engage participants in public health research and the ethical context in which that occurs. Supporting the ethical conduct of internet research will benefit those involved in research, including researchers, HRECs, organisations and research participants.